2014
DOI: 10.1002/nmi2.48
|View full text |Cite
|
Sign up to set email alerts
|

Respiratory infection by Corynebacterium striatum: epidemiological and clinical determinants

Abstract: The increasing prevalence of advanced chronic respiratory disease, with frequent exposure to broad-spectrum antibiotics for repeated and prolonged hospitalizations, favours the emergence of nosocomial respiratory infection by Gram-positive bacteria, such as outbreaks of Corynebacterium striatum. There is little evidence about patterns of respiratory infection, transmission and adaptive ability of this pathogen. Seventy-two C. striatum isolates from 51 advanced respiratory patients, mainly chronic obstructive p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
53
0
4

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 48 publications
(63 citation statements)
references
References 32 publications
5
53
0
4
Order By: Relevance
“…It was difficult to classify these infections as nosocomial outbreaks, since very large intervals existed between the sampling dates of these isolates. Recently, Renom et al reported that multidrugresistant C. striatum contributes to high morbidity and mortality (41z) in nosocomial respiratory infection patients (35). Since most patients received long-term hospitalizations in this study, a high level of concern remains regarding the continuous monitoring of C. striatum disseminating in the hospital environment.…”
Section: Discussionmentioning
confidence: 69%
“…It was difficult to classify these infections as nosocomial outbreaks, since very large intervals existed between the sampling dates of these isolates. Recently, Renom et al reported that multidrugresistant C. striatum contributes to high morbidity and mortality (41z) in nosocomial respiratory infection patients (35). Since most patients received long-term hospitalizations in this study, a high level of concern remains regarding the continuous monitoring of C. striatum disseminating in the hospital environment.…”
Section: Discussionmentioning
confidence: 69%
“…In recent years, C. striatum has been found to be a potentially important bacterial pathogen for humans, since it has been isolated from several kinds of sterile samples, including cerebral fluid, arthroedema, and others [2][3][4][5][6]. However, most of the C. striatum strains reported were isolated from the lower respiratory tracts of patients with chronic obstructive pulmonary diseases as well as other specific risk factors [7][8][9]. The other well-known risk factors include a longer hospitalization period and previous use of betalactam antibiotics and invasive devices for diagnosis and treatment [7][8][9].…”
Section: Introductionmentioning
confidence: 99%
“…In the second case it was susceptible to vancomycin, linezolid and erythromycin. Another study in Spain where C. striatum isolates from 51 advanced respiratory patients, mainly chronic obstructive pulmonary disease, and 56.9% specimens had C. striatum isolates in pure culture, in 26.4% they were accompanied by P. aeruginosa, in 8.3% by Stenotrophomonas maltophilia, and by other bacteria in 8.3% cases [17,18]. In second and third case C. striatum is accompanied by P. aeruginosa.…”
Section: Discussionmentioning
confidence: 97%